Comparison of non-linear dynamic frame response under recorded and numerically generated accelerograms - Möller, Oscar; Ascheri, Juan Pablo; Nardi, Leandro Emanuel (Revista de la Construcción. Journal of Construction, 2021)
<span style="font-size: 10.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The time history analysis of the linear and non-linear response of earthquake resistant structures is a tool increasingly used in practice and required by codes. In this paper, a set of 12 accelerograms was generated numerically with the spectral representation methodology. Another set of 15 accelerograms were selected from a database of earthquake records and scaled with a uniform factor so that the mean spectrum fits the design one. The non-linear dynamic response of two frames of different stiffness and resistance was obtained under the action of the two sets of accelerograms. The global force - displacement results showed a higher coefficient of variation for the set of recorded accelerograms, especially for the structure of lower resistance that has a strong non-linear incursion. The same tendency was obtained for the moment - curvature relationships of beam and column sections, with higher dispersions compared to the global results. In addition, the influence of the vertical acceleration component was analyzed, resulting in a higher incidence in the interior columns of the frames.